PENINGKATKAN KEMAMPUAN SPASIAL SISWA SMP MELALUI MODEL KOOPERATIF STAD BERBANTUAN WINGEOM - -, Arcat (Universitas Pasir Pengaraian, 2014)
This research will be revealed differences increase in spatial ability among students who obtain STAD cooperative learning models aided by Wingeom with students who obtain conventional learning. The study was quasi-experimental. The samples in this study were eighth grade students from two classes at one of public secondary school in West Bandung district. The research instrument consists of a set of tests of spatial ability and observation sheets. The study design used Non Equivalent Control GroupDesign. Both classes were given pretest and posttest on spatial ability. Research hypotheses were tested through parametric test (t-test) and non-parametric tests (Mann- Whitney test). The results showed that an increase in spatial ability of students whoobtain STAD cooperative learning models aided by Wingeom better than students who obtain conventional teaching.